Reconsidering private sector power: business input and local development policy - Reese, Laura A.; Rosenfeld, Raymond A. (2002)
This article raises questions about several key assumptions about business involvement in local policy making generally and in local development policy specifically. At issue is the nature and extent of systemic business influence and the nature of public policies that result. Based on data from a survey of 350 cities in Canada and the United States and nine case studies, the authors conclude that business interests are not unitary nor cohesive within cities, the composition and nature of the private sector is not uniform across cities, and that differentiated patterns of business input and policy output can result. The authors ultimately argue that a broader perspective is needed to fully portray the variety of public/private relationships present in cities than the prevalent growth machine or development regime frameworks suggest. The broader construct of local civic culture is provided as a more contextual basis for understanding the myriad roles businesses play in local economic processes. - Reproduced.
Keywords: Economic and social development